2022
DOI: 10.1124/jpet.122.001217
|View full text |Cite
|
Sign up to set email alerts
|

Zhx2 Is a Candidate Gene Underlying Oxymorphone Metabolite Brain Concentration Associated with State-Dependent Oxycodone Reward

Abstract: Understanding the pharmacogenomics of opioid metabolism and behavior is vital to therapeutic success, as mutations can dramatically alter therapeutic efficacy and addiction liability. We found robust, sex-dependent BALB/c substrain differences in oxycodone behaviors and whole brain concentration of oxycodone metabolites. BALB/cJ females showed robust statedependent oxycodone reward learning as measured via conditioned place preference when compared to the closely related BALB/cByJ substrain. Accordingly, BALB/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In addition, the authors suggest that chronic stress 'primes' the opioid system in females and this would promote opioid-associated learning, again a gender-specific response that may account for the known sex differences in opioid use, abuse and in the effects of stress since these changes are not seen in males and the absence of such changes in these parameters may reduce the capacity to support opioid-mediated learning. Beierle et al (2022) found robust sex-dependent substrain differences when comparing the effects of oxycodone in BALB/cj and BALB/cByj mice. In CPP, the female BALB/cj mice spent more time in the side associated with oxycodone than the BALB/cByj mice, showing enhanced sensitivity to oxycodone, whereas the male strains did not differ.…”
Section: Sex Differences In Abuse Liability Of Oxycodone -Animal Studiesmentioning
confidence: 93%
“…In addition, the authors suggest that chronic stress 'primes' the opioid system in females and this would promote opioid-associated learning, again a gender-specific response that may account for the known sex differences in opioid use, abuse and in the effects of stress since these changes are not seen in males and the absence of such changes in these parameters may reduce the capacity to support opioid-mediated learning. Beierle et al (2022) found robust sex-dependent substrain differences when comparing the effects of oxycodone in BALB/cj and BALB/cByj mice. In CPP, the female BALB/cj mice spent more time in the side associated with oxycodone than the BALB/cByj mice, showing enhanced sensitivity to oxycodone, whereas the male strains did not differ.…”
Section: Sex Differences In Abuse Liability Of Oxycodone -Animal Studiesmentioning
confidence: 93%
“…Genetic regulation of gene expression (eQTLs) provides a functional link and causal support for quantitative trait genes/variants underlying behavior 23,43,44,51 . Using a striatal RNA-seq dataset from 23 F2 mice that had undergone OXY-CPP testing, two weeks of high-dose OXY treatment (20 mg/kg, i.p.…”
Section: Cis-expression Qtlsmentioning
confidence: 99%
“…Finally, Phillips and colleagues exploited the reduced genetic complexity between DBA/2J substrains to identify a functional missense mutation in Taar1 that influences methamphetamine-induced hyperthermia, negative reinforcement, and toxicity [38][39][40][41][42] . Our lab also extended the RCC approach to BALB/c substrains, where we quickly identified candidate genes for nociceptive sensitivity, brain weight, and opioid behavioral and molecular traits 43,44 .…”
Section: Introductionmentioning
confidence: 99%